TRAINER FUZZY SEBAGAI SARANA PRAKTIKUM MAHASISWA - Muhammad Lutfi Mahasinul Akhlak; Adi Kristanto (STMIK BINA PATRIA, 2022)
Fuzzy Logic Lecture material is taught with the aim that students understand the basic concepts of Fuzzy Logic. The results of the questionnaire on 10 student respondents showed that respondents did not understand fuzzyfication theory (40%), inference theory (40%) and defuzzyfication theory (60%), this was due to the absence of practical tools. Therefore, the purpose of this research is to make a Fuzzy Trainer as a means of student practicum. The research method uses Research and Development Methods with the ADDIE development model through five stages of development, namely; (1) Analysis, (2) Design, (3) Development, (4) Implementation and (5) Evaluation. The result of the research is a Fuzzy Trainer which has 3 modules that have been tested. The first module aims to control LED brightness using 2 potentiometers. The second module aims to control the speed of the DC motor using 2 potentiometers. The third module aims to control the speed of the DC motor using the DHT11 sensor. The test results show that all scenarios were successfully tested in all modules. This indicates that the Fuzzy Trainer is functioning properly. Based on filling out questionnaires by respondents which contained a manual book and then practiced by respondents, it was concluded that this practicum tool is easy to assemble, easy to use and makes it easier for students to understand Fuzzy Logic theory with the majority of respondents strongly agreeing (SS) amounting to 86.1% and agree (S) by 13.6%. Keywords: Trainer, Fuzzy Inference System, Mamdani, Atmega328P, Practicum